Two new species of the genus Hishimonus (Hemiptera: Cicadellidae) with a new record from India - Meshram, Naresh M.; Chaubey, Rahul (Zootaxa, 2016)
Two new species of leafhoppers, Hishimonus nauniensis sp. nov. (from Himachal Pradesh: Solan) and Hishimonus pantanagarensis sp. nov. (from Uttarakhand: Pant Nagar) from India, are described and illustrated. Also, the species Hishimonus thapai Virakatamath and Mohan, previously known only from Nepal is illustrated with a new record for India.